Pengembangan LKPD Berbasis Augmented Reality pada Materi Kombinasi Gerak Dasar dalam Permainan Bola Besar Siswa Sekolah Dasar - Deswita Adriani; Aref Vai; Agus Prima Aspa; Muhammad Imam Rahmatullah; Kristi Agust; Rola Angga Lardika (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2026)
Abstract Physical Education learning in elementary schools requires instructional media that can bridge theoretical explanations and movement practice so that students can better understand fundamental movement combinations in invasion games. This study aims to develop and evaluate the feasibility of an Augmented Reality–based student worksheet (LKPD) on combinations of locomotor, non-locomotor, and manipulative movements in soccer, volleyball, and basketball for elementary school students. The research employed a research and development design using the Plomp model (preliminary research, prototyping, and assessment), involving a content expert, language expert, media expert, a Physical Education teacher, and 39 sixth-grade students at an elementary school in Pekanbaru. Data were collected through expert validation sheets and practicality questionnaires and analyzed descriptively using a Likert scale. The results show that the Augmented Reality–based worksheet obtained an average validation score of approximately 3.92 out of 4.00 (valid category) and a practicality score of about 55.08 out of 60 (practical to very practical), indicating that it is appropriate to be used as an instructional medium for Physical Education learning on invasion games in elementary schools.​